SISTEM PENDINGINAN MESIN SUZUKI CARRY ST 100 - , SUNIKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Car engine is at work will generate heat due to combustion process. If the heat caused by the greater, there will be overheating. Overheating can affect engine work, especially in the engine lubrication system. The most extreme thing that expansion will occur in the parts of the machine. To prevent this does not happen, then we need a cooling system so that the engine temperature is maintained at normal temperatures. The process of cooling using coolant flows from the radiator. The coolant lines will be streamed to a line that is next to the engine cylinders. With the temperature so the engine heat will be transmitted to the coolant and coolant which receives heat from the engine to the radiator to be cooled again with the help of a cooling fan. With the cooling system, the working temperature of the engine will always be awake and working machines will always be optimal.